PERILAKU KEUANGAN UNTUK AKUNTANSI ZAKAT DENGAN STANDAR PSAK 109 PADA LEMBAGA KEUANGAN MIKRO SYARIAH (STUDI KASUS PADA PERLAKUAN ZAKAT PADA KSPPS BMT SURYA RAHARJA) - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine financial behavior in the application of zakat accounting with the PSAK 109 standard in the Baitul Maal Wat-Tamwil (BMT) Islamic Financing Cooperative (KSPPS) Surya Raharja. The research method used is descriptive qualitative, the technique is to compare company data with concepts and theories to produce real data with the validity obtained from data triangulation. The results of research on accounting behavior for zakat accounting on the basis of PSAK 109 in KSPPS BMT Surya Raharja can be said that many things are in accordance with PSAK 109, but there is one thing that is not appropriate, namely the placement of zakat funds in the financial statements is not separated into reports zakat funds but mixed with other financial reports. and Zakat funds in LKMS are still limited to cash funds.